Grammarly: An instructional intervention for writing enhancement in management education - Calma, Angelito; Cotronei-Baird, Valeria; Chia, Austin (The international journal of management education, 2022)
To ensure that graduates are adequately prepared for the workplace, writing skills is increasingly regarded as an important outcome of management education; hence, there is a need to improve students' writing skills alongside giving ongoing scholarly attention to providing pedagogical and practical guidance for management educators. In this paper, we present the findings of a study that examined the usefulness of Grammarly – a digital writing assistance tool – for supporting management educators and students. Using a sample of one hundred 2000-word group reports from a masters business analysis subject, we examine feedback from Grammarly to determine its usefulness as an instructional tool for improving students' written work. While Grammarly detects twelve types of writing issues (i.e. formality, variety in vocabulary, concision, clarity, conventions, grammar, sensitivity, fluency, readability, punctuation, and spelling) our results demonstrate that the breadth and depth of feedback provided by Grammarly can be used as more than an error detection tool. We discuss some of the implications for higher education arising from this, and offer suggestions for incorporating Grammarly as an instructional tool in management education to enhance students' writing skills. •Writing skills for management students is important and valued by employers.•Grammarly detected writing issues on a sample of student assignments.•Assignments show issues around correctness, clarity, engagement and delivery.•Analysis of twelve writing sub-dimensions reveal further specific issues.•Grammarly can be used as an instructional tool to improve students' writing skills.